الثدييات الفطرية في شمال غرب ليبيا و دور الأمطار والحرارة في توزيعها الجغرافي - بسيسة, حامد البشير; عاشور, محمد فيصل; الجديدي, طارق بشير (The Libyan Journal of Science, 2019)
This study was conducted on mammals in the western part of the Jafara Plain and on its relationship to environmental factors, such as temperature and rainfall. This study included two parts; the first part is a field study to identify the species of wild mammals in the western part of the Jafara plain and to determine its geographical distribution. The second part of this study included analyzing data of average annual rainfall and average annual temperatures, using the regression equation and the quintile equation for eight urban areas within the region during thirty years, from 1977 to 2006 due to the availability of temperature and precipitation data in this period. The results showed that there are nineteen species of wild mammals in this region belonging to ten families of six orders. The most recorded species belong to the order of rodents (47%) followed by the order of carnivores (26%), then insectivores (10%). Results of environmental changes showed that, the trend in all studied areas was negative and that the amounts of rain were fluctuating, unstable and decreased at a rate between 40 - 125 mm during the thirty years. As for the temperature, it rose during this period between 1.5oC to 2oC. Therefore, it became clear that the change in environmental factors caused an increase in the rate of drought, and this is what threatens the natural vegetation and thus threatens all other organisms, especially wild mammals, which their numbers were few in the driest places on the plain of Jafara.